Combating Infectious Diseases Threat among Students in Islamic Boarding School (Pondok Pesantren): A Pilot Assessment - Ichlasul Amalia; Fajrul Falah Farhany; Meyka Budi Rachmawati; Winda Ernia; Hanggoro Tri Rinonce; Happy Indah Kusumawati; Rahadyana Muslichah (Journal of Community Empowerment for Health, 2023)
Pondok Pesantren or Islamic Boarding Schools (IBS), as one of the major boarding-based education systems in Indonesia, face significant challenges in preventing and controlling infectious disease transmission. Huge numbers of students, crowded dormitories, shared lavatories, limited healthcare facilities, and intense social interactions increase the risk of transmitting infectious diseases within the facilities. This study aimed to provide an initial assessment of the history of infectious diseases and the spread of infectious diseases among students living in IBS before conducting training and intervention related to infectious diseases prevention and control programs. This quantitative study was conducted using a descriptive analysis approach in July-August 2022 at Assalafiyyah Mlangi II Terpadu IBS. A non-probability sampling with total sampling of 841 students was used. The data were collected using self-administered questionnaires developed on Google Form and imported to Microsoft Excel for further data analysis. The results indicate that the majority of the students have a history of infectious diseases (90.48%) during their time living in IBS. The most common infectious diseases found were influenza (55.38%), scabies (20.20%), conjunctivitis (8.13%), varicella (4.54%), herpes simplex (2.08%), tuberculosis (0.65%), and measles (0.13%). During the COVID-19 pandemic, a total of 21.16% of the students had been exposed to COVID-19. Considering these findings, it is essential for the staff and students living in IBS to understand the steps to prevent the occurrence of infectious diseases and be able to identify and provide initial treatment to stop the transmission of the disease. The development of digital health intervention using a website or application can be implemented to help the students report and consult case findings to medical experts.